Understanding the internal states of others by listening to action verbs. (August 2016) - Di Cesare, G.; Fasano, F.; Errante, A.; Marchi, M.; Rizzolatti, G.
Abstract: The internal state of others can be understood observing their actions or listening to their voice. While the neural bases of action style (vitality forms) have been investigated, there is no information on how we recognize others' internal state by listening to their speech. Here, using fMRI technique, we investigated the neural correlates of auditory vitality forms while participants listened to action verbs in three different conditions: human voice pronouncing the verbs in a rude and gentle way, robot voice pronouncing the same verbs without vitality forms, and a scrambled version of the same verbs pronounced by human voice. In agreement with previous studies on vitality forms encoding, we found specific activation of the central part of insula during listening to human voice conveying specific vitality forms. In addition, when listening both to human and robot voices there was an activation of the posterior part of the left inferior frontal gyrus and of the parieto-premotor circuit typically described to be activated during observation and execution of arm actions. Finally, the superior temporal gyrus was activated bilaterally in all three conditions. We conclude that, the central part of insula is a key region for vitality forms processing allowing the understanding of the vitality forms regardless of the modality by which they are conveyed. Highlights: Vitality forms characterize how actions and words are displayed. Listening to gentle and rude vitality forms induces the activation of the central insula. The central part of insula is a key region for vitality forms processing.